Gel properties of myofibrillar proteins heated at different heating rates under a low-frequency magnetic field. (15th August 2020) - Wang, Xian; Xia, Minquan; Zhou, Yuanhua; Wang, Limei; Feng, Xiaolong; Yang, Kun; Ma, Jing; Li, Zhenshun; Wang, Lan; Sun, Weiqing
Highlights: MP heated at 2 °C/min under a 9.5 mT magnetic field had increased WHC. The content of ionic and hydrogen bonds increased at 2 °C/min with 9.5 mT. Unfolding of α-helix at 2 °C/min with 9.5 mT improved the microstructure of gel. The treatment of 2 °C/min under 9.5 mT reduced hydrophobic interactions. Abstract: The effects of low-frequency magnetic field combined with different heating rates on pork myofibrillar protein (MP) gels were investigated. Samples were treated under different heating rates (1 °C/min and 2 °C/min) in the presence or absence of 9.5 mT low-frequency magnetic field. The highest levels of intermolecular and intramolecular ionic and hydrogen bonds in MP were observed at the heating rate of 2 °C/min under the 9.5 mT magnetic field. These bonds resulted in decreasing the α-helix and increasing the β-sheet and β-turn, which promoted the formation of a more uniform microstructure. It also increased the proportion of bound water, increasing the ability of MP to bind with water. This effect, combined with the weaker hydrophobic interactions, as confirmed by the reduced content of tryptophan and aliphatic residues, explained well the high water-holding capacity of MP induced by heating at 2 °C/min under the 9.5 mT magnetic field.